Gender differences in pancreatic neuroendocrine neoplasms: A retrospective study based on the population of Hubei Province, China - Fu, Mengfei; Yu, Li; Yang, Liu; Chen, Yang; Chen, Xiao; Hu, Qinyu; Sun, Hui (Frontiers in Endocrinology, 2022)
Objective: The aims of the present study were to investigate gender differences in the clinicopathological features, distant metastasis and prognosis of pancreatic neuroendocrine neoplasms (pNENs) in a Chinese population, and to identify any important gaps in the classification and management of pNENs relative to gender. Methods: Retrospective collection of the clinicopathological data of 193 patients with pathologically confirmed pNENs were analyzed and follow up was extended to observe the prognosis of the disease. Differences between genders in basic characteristics, clinical symptoms, comorbidities, and tumor parameters were analyzed. Results: There was no significant difference in females and males, however, moderately higher for females (52.8% vs. 47.2%), with the largest subgroup being 40~60 years of age (54.9%). Age at onset (P=0.002) and age at diagnosis (P=0.005) were both younger in females compared to males. Males lived more in urban areas and females lived more in rural areas (P=0.047). The proportion of smokers and alcohol drinkers was significantly higher in males than in females (P < 0.001). Non-functional pNENs were more frequent in males and functional pNENs in females (P=0.032). In women, functional status of the tumor was significantly associated with metastatic outcome (P=0.007) and functional tumors proved to be a protective factor compared to non-functional tumors (OR=0.090,95% CI: 0.011~ 0.752). There were no gender differences in tumor size, location, grade, stage or prognosis. Conclusions: Gender differences in some clinicopathological features, and distant metastasis in patients with pNENs were identified, which suggested certain management details that justified emphasis based on gender.